Writing the heavenly frontier : metaphor, geography, and flight autobiography in America 1927-1954 - Turner, Denice H., 1964- (Costerus ;, 2011)
Writing the Heavenly Frontier celebrates the early voices of the air as it examines the sky as a metaphorical and political landscape. While flight histories usually focus on the physical dangers of early aviation, this book introduces the figurative liabilities of ascension. Early pilot-writers not only grappled with an unwieldy machine, they also grappled with poetics that were extremely selective. Tropes that cast Charles Lindbergh as the transcendent hero of the new millennium were the same ones that kept women, black Americans, and Indigenous peoples imaginatively tethered to the ground.